A History of Childhood Trauma and Response to Treatment With Antipsychotics in First-Episode Schizophrenia Patients: Preliminary Results. Issue 10 (October 2016) - Misiak, Błażej; Frydecka, Dorota
Abstract : Abstract: In this study, we aimed to investigate whether a history of childhood trauma (CT) can help predict early response to antipsychotic treatment in patients with first-episode schizophrenia (FES). We recruited 64 FES patients who were followed up after 12 weeks of treatment with second-generation antipsychotics. Symptomatic manifestation was examined using the Positive and Negative Syndrome Scale (PANSS). Childhood adversities were assessed using the Early Trauma Inventory Self-Report—Short Form. Nonresponders had significantly higher general trauma score, emotional abuse score, total trauma score, and baseline PANSS negative factor score. A history of CT was significantly more frequent among nonresponders. Logistic regression analysis revealed that positive history of CT, higher emotional abuse score, and higher baseline PANSS negative factor score are significant predictors of poor response to treatment. Our results indicate that a history of CT, especially emotional abuse, and higher severity of negative symptoms are independent predictors of poor response to treatment with antipsychotics.